Weighted Watson-crick automata and applications in halal authentication - Mohd Tamrin, Mohd Izzuddin; Turaev, Sherzod; Che Azemin, Mohd Zulfaezal (2016)
The process of verifying the autheticity of imported meat or processed meat is a very challenging task and there is no guarantee that the meat in Malaysia are not conteminated with non halal meat. In our research project, we propose an alternative, cheaper and automated approach to the auhtentication of meat product on the weighted Watson-crick automata. We mainly study the theoretical problems that include probabilistic and fuzzy variants such as the generative capacities, closure properties and complexity problems. We also construct formal models for food authentication processes and develop algorithms for the identification of non halal patterns in DNA molecules. Our investigations have created new theorems and algorithms used in the design of automated halal authentication tools. From our simulation, we observed that the performance of our algorithms is promising with strong sensitivity and high specificity of 80% and 90% respectively.